Pengembangan Media Maket Pada Mata Pelajaran Desain Pemodelan Jalan dan Jembatan di SMK Negeri 1 Kemlagi - Muhammad Rizqi; Purwo Mahardi (Jurnal Kajian Pendidikan Teknik Bangunan, 2025)
The research was motivated by several problems those in the field, one of them is the selection of inappropriate learning media has an influence on student learning outcomes. The aim of this research is to adapt the model media to the students, knowing students' responses to learning using mock-up media, and find out the students' learning outcomes from the development of model media in learning. This research is a type of development research or Research and Development (R&D), which this research was conducted at SMK Negeri 1 Kemlagi with 11th grade students majoring in Building Modeling and Information Design as the subjects of the research. The data collection technique uses a questionnaire method containing a validation questionnaire, response, and understanding test. he percentage of media suitability got a value of 88.5%, media suitability got a value of 93%, student responses got a value of 90%, and learning outcomes got a value of 83.8%, Therefore the development of road and bridge model media is declared very feasible and very appropriate and has a good response from students along with satisfactory learning outcomes.